Fracionamento do fósforo orgânico em solo adubado com esterco bovino - Braos, Lucas Boscov [UNESP] (2013)
Normally the available P evaluation methods evaluate soil inorganic P (Pi), ignoring the P organic (Po) fractions. Pi usually controls the P availability in tropical soils, but the Po contribution should not be neglected, mainly in systems with low P input or management systems that support the organic matter accumulation. The aims of this study were evaluate the changes in the Po fractions over time, in soil fertilized and non fertilized with manure, and correlate forms of Po with available P extracted by anion exchange resin. The experimental design was a randomized block in factorial scheme 2 x 9, wherein the first factor is the manure presence (20 t ha-1) or absence, and the second are the sampling times (3, 7, 14, 21, 28, 49, 70, 91 e 112 days) after manure incorporation. The experiment was carried out in field conditions, in a sand clay loam Haplustox. In the soil samples collected in each sampling time it was determined labile, moderately labile and non-labile Po. The manure fertilization caused an increase in the Po levels on the moderately labile and non-labile fractions, and in the total organic P. On average 5.1% of total Po was in labile, 44.4% in moderately labile and 50.5% in non-labile fractions. The moderately labile Po and non-labile Po fractions correlated with the resin-P, indicating that the two fractions influence the available P to plants and, therefore, the application of manure increases the ability of soil to restore the available P. The labile and non-labile Po fractions have changed over the sampling times, but there was no defined trend